2016
DOI: 10.1371/journal.pone.0138418
|View full text |Cite
|
Sign up to set email alerts
|

207-nm UV Light—A Promising Tool for Safe Low-Cost Reduction of Surgical Site Infections. II: In-Vivo Safety Studies

Abstract: BackgroundUVC light generated by conventional germicidal lamps is a well-established anti-microbial modality, effective against both bacteria and viruses. However, it is a human health hazard, being both carcinogenic and cataractogenic. Earlier studies showed that single-wavelength far-UVC light (207 nm) generated by excimer lamps kills bacteria without apparent harm to human skin tissue in vitro. The biophysical explanation is that, due to its extremely short range in biological material, 207 nm UV light cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
116
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 48 publications
8
116
1
11
Order By: Relevance
“…In agreement with our previous results using 207-nm light (7,8), here we showed that 222-nm light has similar antimicrobial properties as a conventional germicidal lamp but without causing mammalian skin damage.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our previous results using 207-nm light (7,8), here we showed that 222-nm light has similar antimicrobial properties as a conventional germicidal lamp but without causing mammalian skin damage.…”
Section: Introductionsupporting
confidence: 93%
“…One group of three mice was exposed to fluence of 157 mJ/cm 2 from 222 nm light delivered in a 7 h period by a filtered Kr-Cl excimer lamp while another group of three mice was sham irradiated to zero UV fluence. Mice exposed to 157 mJ/cm 2 delivered in 7 h period from 254 nm light represented the positive controls (8).…”
Section: Mouse Irradiationsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, far-UVC light in the 207-to 222-nm range has been demonstrated to effectively inactivate airborne aerosolized viruses. While preliminary findings from in vivo rodent models and in vitro three-dimensional (3-D) human skin models appear favorable to not cause damage to human skin and eyes (90,91), further research must be conducted to verify the margin of safety before implementation. If implemented safely, UVC and UVGI light offers a range of potential disinfectant strategies for buildings and is a common strategy for deep clean practices in health care settings.…”
mentioning
confidence: 99%